The Change in William I. Thomas’s View of Biology - Remisiewicz, Łukasz (Stan Rzeczy, 2018)
In this article the author shows how the exploding role of biology in William Thomas’s sociology and social psychology has changed. Since the beginning of his career, this researcher addressed numerous topics that involved both biological and social factors – he commented on the nature of gender, race, instincts, prejudice and evolution. His departure point was biologism, which proclaimed that innate predispositions are a variable independent of social processes. In the following years, Thomas changed his beliefs, recognising that it was culture and society that left its mark on physiological and psychological development. The changes in Thomas’s reasoning are described by the author against the background of past and present views on the relationship between society and the brain, claiming that his late views could resonate with today’s approaches.